Catestatin as a New Prognostic Marker in Stable Patients with Heart Failure with Reduced Ejection Fraction in Two-Year Follow-Up - Wołowiec, Łukasz (Dis Markers, 2020)
Background and Purpose. The main goal of the study was to assess the usefulness of plasma concentrations of catestatin as a predictor of a composite endpoint (CE): unplanned hospitalization and death for all causes in patients with HFrEF in the midterm follow-up. Experimental Approach. The study group consisted of 52 Caucasian patients in NYHA classes II and III. The control group consisted of 24 healthy volunteers. The biomarkers, whose concentration was assessed before and after physical exertion as well as the variability of their concentration under the influence of the physical exertion, were NT-proBNP, troponin T, and catestatin. Key Results. During the 24-month follow-up period, 11 endpoints were recorded. The univariate analysis of the Cox proportional hazard model showed a statistically significant effect of all assessed CST concentrations on the occurrence of CE. In the 24-month follow-up, where the starting concentration of catestatin was compared with other recognized prognostic factors in HF, the initial concentration of catestatin showed statistical significance in CE prognosis as the only parameter tested. Conclusions. Plasma concentration of catestatin before and after physical exertion is a valuable prognostic parameter in predicting death from all causes and unplanned hospitalization in the group of patients with HFrEF in the 2-year follow-up.